2022
DOI: 10.1186/s12929-022-00830-1
|View full text |Cite
|
Sign up to set email alerts
|

A booster dose of Delta × Omicron hybrid mRNA vaccine produced broadly neutralizing antibody against Omicron and other SARS-CoV-2 variants

Abstract: Background With the continuous emergence of new SARS-CoV-2 variants that feature increased transmission and immune escape, there is an urgent demand for a better vaccine design that will provide broader neutralizing efficacy. Methods We report an mRNA-based vaccine using an engineered “hybrid” receptor binding domain (RBD) that contains all 16 point-mutations shown in the currently prevailing Omicron and Delta variants. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 40 publications
3
27
1
1
Order By: Relevance
“…Lee et al [ 13 ] discussed that only vaccine schedules with at least one mRNA vaccine and a booster dose would trigger a sufficient neutralization response against Omicron.…”
Section: To the Editormentioning
confidence: 99%
“…Lee et al [ 13 ] discussed that only vaccine schedules with at least one mRNA vaccine and a booster dose would trigger a sufficient neutralization response against Omicron.…”
Section: To the Editormentioning
confidence: 99%
“…A recent study showed that the SARS-CoV-2 mRNA-LNP vaccine boost in naïve individuals elicited an increased plasma neutralizing antibody response but a variable antibody response breadth compared to the convalescent individuals 72 . Since the inclusion of the Omicron variant provided minimal gains in protective efficacy against new SARS-CoV-2 strains, their impact on the SARS-CoV-2 pandemic remains unknown [73][74][75][76] . While the B cell response breadth against HCMV gB did not benefit from multivalent vaccines in these studies, a higher magnitude T cell response was elicited against monovalent vaccine-mismatched gB genotype, implying that the multivalent HCMV glycoprotein immunization should be considered as a strategy for those vaccines that seek to enhance T cell response breadth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the timing of boosting should be optimized, as preexisting immunity may compromise the effect of the booster dose [ 130 , 242 ]. Notably, animal studies also found Omicron-specific vaccines induced potent antibodies and immunity against Omicron but not the ancestral strain in vaccine-naive mice and Syrian hamsters [ 241 243 ]. A serological study of vaccine-naive individuals infected with Omicron also showed that their sera contain nAbs against Omicron but not the other variants [ 244 ].…”
Section: Next-generation Vaccinementioning
confidence: 99%